(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
Since the establishment of the Department of Turkic Studies at the Faculty of Oriental Studies of Yerevan State University, a certain place has been devoted to the study and teaching of Turkic epics, which has been carried out within the framework of teaching Turkish literature. Any national epic can certainly form the basis of literature. From this perspective, Turkic epics have had a significant impact on the process of establishing the literature of the Turkic-speaking peoples, taking into account the centuries-old tradition of oral speech and culture. At the same time, they still continue to condition the process of national cultural and identity formation among some Turkic-speaking peoples, while serving as unique national symbols. In particular, “Dede Korkut”, being the ethnogonic epic of various Turkic ethnic groups, still plays a crucial role in popularizing the ideology of Pan-Turkism, naturally, sometimes through the artificial equalization and identification of various national versions. The “Koroglu” (“Keroglu”) epic, created and formed in a later period, taking into account the existence of a larger number of national versions, no longer has the symbolic pan-Turkic significance attributed to “Dede Korkut”. However, in some cases, it also contains elements of national self-identity, and is sometimes considered on the same plane. From the above-mentioned points of view, in particular, for Armenian Turkology, the study of not only the mentioned but also other Turkic epics and the establishment of teaching with the appropriate methodology represent a necessity, which can certainly have scientific and practical significance. The article was prepared based on a summary of the results of our research conducted on the topic in recent years, as well as the conclusions and observations made during the process. One of the notable problems with the topic is its presentation without highlighting the Armenian environment and Armenian epic substratum, which is typical of foreign Turkic studies centers, but in our case, taking into account the existing peculiarities and already recorded results, the use of the same approach is not correct and effective. In this context, knowledge of Turkic languages, as well as certain knowledge of Armenian folklore, is important. Accordingly, the subject can certainly have interdisciplinary significance. By highlighting the specificities of the topic and the problems identified, the methodological approaches considered necessary for teaching the course are presented. As a result of teaching the subject, the Turkologist student can further strengthen such skills as deep knowledge of the topic, comprehensive analysis and comparison of various data.